Equal performance of HTK-based and UW-based perfusion solutions in sub-normothermic liver machine perfusion - Bettina Leber; Sabrina Stimmeder; Kathrin Briendl; Jennifer Weber; Lisa Rohrhofer; Ariane Aigelsreiter; Tobias Niedrist; Robert Sucher; Philipp Stiegler (Scientific Reports)
Abstract Machine perfusion (MP) is gaining importance in liver transplantation, the only cure for many end-stage liver diseases. Varieties of different MP protocols are available. Currently, various MP protocols are available, differing not only in perfusion temperature but also in the specific perfusion solution required. We aimed to investigate the performance of an HTK-based perfusate during sub-normothermic MP (SNMP) of discarded human liver grafts compared to that of a UW-based solution. Twenty discarded livers (rejected for transplantation by all centers) were subjected to ex-vivo SNMP at 21°C with either HTK- or UW-based solution for 12 h. Perfusate and tissue samples collected before the start, after 6 h, and at the end of SNMP were analyzed for liver enzymes, along with mRNA expression of perfusate and tissue markers associated with organ damage. Hepatocellular viability was assessed by measuring bile production, monitoring pH stability, and analyzing histological changes in HE stained tissue sections. After propensity score matching 16 livers were analyzed. Overall, no differences between HTK- and UW-based solution were detected, except for an increased MLKL mRNA expression and impaired pH stability during SNMP with HTK-based perfusate. No other investigated parameters of cell injury, inflammation or hepatocellular viability supported this finding. Bile production was higher in the 6 HTK-perfused livers compared to the three UW-perfused livers that produced bile. Overall, these findings suggest that HTK performs comparably to a UW-based solution during 12 h of liver SNMP.